Quinolone binding to DNA is mediated by magnesium ions. - Palù, G (1992)
The binding of plasmid DNA to norfloxacin, a quinolone antibacterial agent, was investigated by fluorescence, electrophoretic DNA unwinding, and affinity chromatography techniques. The amount of quinolone bound to DNA was modulated by the concentration of Mg2+. No interaction was evident in the absence of Mg2+ or in the presence of an excess of Mg2+, whereas maximum binding was observed at a Mg2+ concentration of 1-2 mM. The experimental data can be fitted to the formation of three types of Mg adducts: a binary adduct with norfloxacin and Mg2+, a binary adduct with DNA and Mg2+, and a ternary adduct with quinolone, plasmid, and Mg2+. We propose a model for the ternary complex, in which Mg acts as a bridge between the phosphate groups of the nucleic acid and the carbonyl and carboxyl moieties of norfloxacin. Additional stabilization may arise from stacking interactions between the condensed rings of the drug and DNA bases (especially guanine and adenine), which may account for the preference exhibited by quinolones for single-stranded and purine-rich regions of nucleic acids. Other possible biochemical pathways of drug action are suggested by the observation that norfloxacin binds Mg2+ under conditions that are close to physiological.